Political Connection and BPD Performance - Tulung, Joy Elly; Ramdani, Dendi (International Research Journal of Business Studies, 2023)
The political situation that stable and conducive simplify business activities of a company politics and vice versa can be facilitated by the existence of good business. The relationship is what eventually called a political connection. Business relationship with politics has a very close relationship to harmony of an economy. The sample in this study is board members in 26 BPD during the year 2010 to 2014. We use political connected as an independent variable, the political connected is the board are coming from government, BPD is owned by government so the board with government background is identified as a political connected. The dependent variables are return on asset, return on equity and non-performing loan. This study uses firm size as a control variable. This study is expected to give a contribution to the topics of political connection and give a recommendation to government how to choice the member of board.